2020
DOI: 10.1002/pip.3339
|View full text |Cite
|
Sign up to set email alerts
|

Interdigitated back‐contact double‐heterojunction GaInP/GaAs solar cells

Abstract: Interdigitated back‐contact (IBC) silicon solar cells are coming of age, but the potential of IBC configurations for compound semiconductor solar cells is yet to be explored. We outline an approach to generalize the diffusion‐driven charge transport (DDCT) method, previously studied for IBC light‐emitting diodes, to develop DDCT solar cells, enabling an IBC double‐heterojunction structure. In particular, we simulate and compare the electrical performance of a GaInP/GaAs DDCT solar cell with an ideal one‐dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[ 19 ] We have previously suggested diffusion‐driven charge transport (DDCT) as a possible alternative for the DHJ based current injection method to overcome its limitations. [ 20,21 ] Following the originally computational introduction of the DDCT method, III‐nitride diffusion injected light emitting diodes (DILEDs) [ 22,23 ] were fabricated and characterized. In spite of being the first experimental demonstration that bipolar diffusion can transport electrons and holes into the active region located outside the pn‐junction and a proof of the DDCT concept, DILED suffered from parasitic yellow luminescence emission, inferior injection efficiency due to the highly n‐doped layer between the MQW and p‐type GaN, and high resistivity metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] We have previously suggested diffusion‐driven charge transport (DDCT) as a possible alternative for the DHJ based current injection method to overcome its limitations. [ 20,21 ] Following the originally computational introduction of the DDCT method, III‐nitride diffusion injected light emitting diodes (DILEDs) [ 22,23 ] were fabricated and characterized. In spite of being the first experimental demonstration that bipolar diffusion can transport electrons and holes into the active region located outside the pn‐junction and a proof of the DDCT concept, DILED suffered from parasitic yellow luminescence emission, inferior injection efficiency due to the highly n‐doped layer between the MQW and p‐type GaN, and high resistivity metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…1(c) and (d) and excludes the contact pads and the thick-substrate region for simplicity. A more detailed description of the model can be found in, for example, [7], [8].…”
Section: Device Modelingmentioning
confidence: 99%
“…Fabrication of compound semiconductor-based DDCT devices is not established due to the unconventional device structures and lack of appropriate lateral doping techniques. So far, experimental studies on DDCT-LEDs have focused merely on GaN devices [10], [21], [22], [23], [24], while GaAs devices have been considered only theoretically [7], [8], [9]. The first report of GaN-based DDCT-LEDs by Riuttanen et al [10] demonstrated the fundamental principle of DDCT by injecting holes into AR through an n-GaN layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation